Terapi zikir terhadap peningkatan resiliensi penderita Low Back Pain (LBP) - Ummil Khairiyah; Yayi Suryo Prabandari; Qurotul Uyun (Jurnal Ilmiah Psikologi Terapan, 2015)
Resilience is needed to improve the condition of subjects, therefore they become stable and able to receive and adjust to their illness gradually. This research examined the effectiveness of zikir therapy for helping patient with low back pain in enhancing their resilience. This research was a quasi experiment (non randimized pretest – posttest control group design) with 11 participants who had low and midlle level of resilience. They were between 45-70 years old, and classified into two groups. One group received the zikir therapy, the other served as a controlled group. The resilience level was measured based on resilience scale from Connor-Davidson scale (scale). The item analysis result showed the alpha cronbach score = 0,924. The hypotesis was tested by Mann Withney. The result showed that the resilience level in experimental group significantly increased after treatment by zikir therapy compare than the control group. After the follow up periode showed that subject in experimental group able to maintained the therapy’s effect for two weeks after the treatment. The conclusion from this research is the zikir therapy is effective in enhancing resilience at patient with low back pain.